PATRIARCHY CULTURE OF TOULA'S FAMILY IN THE BIG FAT GREEK WEDDING MOVIE (2002) - Dewi, Desti Nuryuliyanti; Prihandini, Asih (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
This writing discusses about patriarchy culture of Toula’s family in The Big Fat Greek Wedding movie. Patriarchy culture is a social system in which men hold and control power. It is still found in many societies around. The Big Fat Greek Wedding tells about a Greek woman who falls in love with a non-Greek man and struggles for her family to accept the man as they confront their heritage and cultural identity. The purpose of this writing is to show that Toula’s family in this movie still adheres and resistances to patriarchy culture. Method used in this writing is qualitative method. Qualitative method is a method that involves an interpretive, description, creative, and unique, in the sense of understanding the subject matter. The data are collected and analyzed based on the perspective of literary criticism. The direct conversation and some gestures display related with patriarchy culture are taken. It is found that Toula’s father as the head of the family seems to have the power to take the decision for his family, meanwhile Toula as the child and Maria as the wife do not have. Based on the theories taken, patriarchy in this movie includes in private patriarchy. Private patriarchy originates in the home area as the first and foremost area of men's power over women. So, it shows that Toula’s family still holds the patriarchy culture. Keywords: Patriarchy, Gender Inequality, Gender Roles, Greek